MIXED MESODERMAL TUMOUR - Begum, Nazakat; Bano, Aniqa; Mohammad, Gul (Journal of Ayub Medical College Abbottabad, 1989)
Mixed Mesodermal tumour of the uterus is a rare tumour. It comes under the classification of sarcoma of the uterus; which only comprises less than 5% of all malignancies arising from the uterus. Out of all other types of sarcomas, Mixed Mesodermal tumour are even less common.1 The author has only seen one case of Mixed Mesodermal tumour of the body of uterus and one case of the vagina in her professional life. The tumours are highly malignant; because the spread is early and blood borne.2 Histologically they could be classified as homologous or heterologous. Diagnostic endometrial curettage helps in the diagnosis.